Accounting misstatements following lawsuits against auditors - Lennox, Clive; Li, Bing (Journal of Accounting and Economics, 2014)
This study investigates whether an auditor's experience of litigation in the recent past affects subsequent financial reporting quality. At the audit firm level, we find accounting misstatements occur significantly less (more) often after audit firms are sued (not sued). At the audit office level, the negative association between past litigation and future misstatements is stronger for offices who were directly implicated in the litigation than for the non-accused offices of sued audit firms. Therefore, the litigation experiences of both audit firms and audit offices are incrementally significant predictors of future financial reporting quality.